PENGARUH KOMPETENSI, INDEPENDENSI DAN INTEGRITAS TERHADAP KUALITAS AUDIT DENGAN ETIKA AUDITOR SEBAGAI VARIABEL PEMODERASI (Studi Empiris pada Kantor Akuntan Publik yang Terdapat di Pekanbaru, Padang, dan Batam) - Amin Surahman; Hardi Hardi; Lila Anggraini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the influence of Competence, Independence, and Integrity to Audit Quality with Auditor’s Ethic as Variable of Moderation. Research carried out on accounting firm of Pekanbaru city, Padang City, and Batam City on 2017. Sample used as respondents were taken by using purposive sampling method. Each population is represented by public accountant office’s auditors. Questionnaires were distributed to 95 respondents, amd successfully reassembled with complete answers obtained from 67 respondents. Data were collected from 67 respondents further data were analized by using software of SPSS version 21.0 using descriptive statistical analysis and multiple linear regression analysis to generate the classical assumption, the model data analysis, coefficient of determinationand prove the hypothesis. The results shows that competence and independence has significant effect to audit quality, while integrity has no significant effect to audit quality. Auditor’s ethic moderate the effect on competence, independence, and integrity to audit quality.Keywords: Competence, Independence, Integrity, Auditor’s Ethic, and Audit Quality.